Neurophysiology of human touch and eye gaze in therapeutic relationships and healing: a scoping review. (February 2019) - Kerr, Fiona; Wiechula, Rick; Feo, Rebecca; Schultz, Tim; Kitson, Alison
ABSTRACT: Objective: The primary objective of this scoping review was to examine and map the range of neurophysiological impacts of human touch and eye gaze, and consider their potential relevance to the therapeutic relationship and to healing. Introduction: Clinicians, and many patients and their relatives, have no doubt as to the efficacy of a positive therapeutic relationship; however, much evidence is based on self-reporting by the patient or observation by the researcher. There has been little formal exploration into what is happening in the body to elicit efficacious reactions in patients. There is, however, a growing body of work on the neurophysiological impact of human interaction. Physical touch and face-to-face interaction are two central elements of this interaction that produce neurophysiological effects on the body. Inclusion criteria: This scoping review considered studies that included cognitively intact human subjects in any setting. This review investigated the neurophysiology of human interaction including touch and eye gaze. It considered studies that have examined, in a variety of settings, the neurophysiological impacts of touch and eye gaze. Quantitative studies were included as the aim was to examine objective measures of neurophysiological changes as a result of human touch and gaze. Methods: An extensive search of multiple databases was undertaken to identify published research in the English language with no date restriction. Data extraction was undertaken using an extraction tool developed specifically for the scoping review objectives. Results: The results of the review are presented in narrative form supported by tables and concept maps. Sixty-four studies were included and the majority were related to touch with various types of massage predominating. Only seven studies investigated gaze with three of these utilizing both touch and gaze. Interventions were delivered by a variety of providers including nurses, significant others and masseuses. The main neurophysiological measures were cortisol, oxytocin and noradrenaline. Conclusions: The aim of this review was to map the neurophysiological impact of human touch and gaze. Although our interest was in studies that might have implications for the therapeutic relationship, we accepted studies that explored phenomena outside of the context of a nurse-patient relationship. This allowed exploration of the boundary of what might be relevant in any therapeutic relationship. Indeed, only a small number of studies included in the review involved clinicians (all nurses) and patients. There was sufficient consistency in trends evident across many studies in regard to the beneficial impact of touch and eye gaze to warrant further investigation in the clinical setting. There is a balance between tightly controlled studies conducted in an artificial (laboratory) setting and/or using artificial stimuli and those of a more pragmatic nature that are contextually closer to the reality of providing nursing care. The latter should be encouraged.